Air particulate matter pollution and circulating surfactant protein: A systemic review and meta-analysis. (June 2021) - Wang, Zhenjie; Xu, Mengmeng; Wang, Yanhua; Wang, Ting; Wu, Nan; Zheng, Wenjing; Duan, Huawei
Abstract: Objective: Air particulate matter (PM) pollution is associated with the alterations in circulating pulmonary damage proteins. But there are not consistent results among the epidemiological studies. The aim of this study is to investigate the alteration of surfactant protein (SP) from PM exposure. Methods: We conducted a comprehensive meta-analysis by searching the databases of PubMed, Medline, EMBASE, Web of Science and CNKI before October 2020 which reported PM pollutants and surfactant protein in the population. The sources of heterogeneity were assessed by subgroup (smoking, particulate matter with different aerodynamic diameter, exposure duration) analysis. We also used the publication bias tests for the comprehensive assessment. Results: This meta-analysis consisted of 10 studies with 1985 subjects. The results showed that the combined standardized mean difference (SMD) value was 0.05, 95% confidence interval (CI) was −0.07 to 0.17 for serum SP-A and −0.81 (95% CI: -1.41 to −0.21) for circulating SP-D. Among smokers, the combined SMD value of SP-A were 0.29 (95% CI: 0.05 to 0.52). We did not find the correlation between publication year of SP-A and SP-D and study heterogeneity. Conclusions: Circulating SP-D was significantly decreased by air particulate matter. Serum SP-A was significantly increased by PM exposure among smokers. Circulating surfactant protein may be considered as a biomarker for respiratory injury caused by air particulate matter. Highlights: Comprehensive analysis on circulating surfactant proteins and air particulate matter in population. PM exposure was associated with a reduction of circulating SP-D. Circulating surfactant protein can be a biomarker for respiratory injury caused by particulate matter.